Physical and chemical effect of impurities in carbon capture, utilisation and storage - Ahmad Amirhilmi A. Razak; Ismail M. Saaid; Muhammad Aslam Md. Yusof; Norhafizuddin Husein; M. Fakrumie Zaidin; Khalik Mohamad Sabil (Journal of Petroleum Exploration and Production Technology, 2023)
Abstract Deployment of carbon capture, utilisation, and storage (CCUS) technologies to mitigate climate change and overturn CO2 emissions growth would require transformational changes comprehensively. The primary focus of this manuscript is on the impurities standards and limitation that can ensure project feasibility in the long run. There is a need in the industry for guidance on purity analysis prior to capture, shipment, and storage of carbon dioxide. This is because the cost to capture and separate the stream is proving to be very costly that can make the project to be unfeasible to operate. Following this further, this manuscript discusses the previous research and best practices that establish standards for acceptable impurities that might present in the stream and its effects towards the CCUS system. Consequently, this manuscript also provides better understanding on the impurities effects towards CCUS technology system in general. Understanding these limitations, may provide cost effective solution for CCUS problems that revolves around the impurities in CO2 stream. Impurities can affect some components of the carbon capture and storage process. It is clear that even a little number of impurities can cause the carbon dioxide stream properties to change. There are two primary factors discussed in this manuscript that affect how a CCUS system responds to a CO2 stream that contains impurities: a physical and chemical effects.